Let $(a_j)$ and $(b_j)$ be non-negative numbers, and for $k\geq 0$ define $c_k=\sum _{j=0}^ka_jb_{k-j}$. I'm trying to show that : $$\sum _{k=0}^{\infty}\frac{c_k^2}{k+1}\leq (\sum _{j\geq 0}a_j^2)(\sum _{j\geq 0}b_j^2).$$

By Cauchy-Schwarz we have $c_k^2\leq (\sum _{j= 0}^ka_j^2)(\sum _{j=0}^kb_j^2)\leq(\sum _{j\geq 0}a_j^2)(\sum _{j\geq 0}b_j^2)$, but the harmonic series diverges, so we can't prove the inequality this way.

By homogeneity we can assume that $\sum _{j\geq 0}a_j^2=1=\sum _{j\geq 0}b_j^2$. It remains to show that $\sum _{k=0}^{\infty}\frac{c_k^2}{k+1}\leq 1$ but I don't see how to proceed for the moment. Any idea will be welcomed.


Using Cauchy product formula we have:

$(\sum_{n=0}^{\infty}a_n^2)(\sum_{n=0}^{\infty}b_n^2)=(\sum_{n=0}^{\infty}d_n)$, where:

$d_n=\sum_{k=0}^{n} a_k^2b_{n-k}^2$

Notice that if we show that:

$\frac{c_n^2}{n+1} \leq d_n$

The inequality will be proven, but it's Cauchy-Schwarz inequality for:


$y_k=a_k b_{n-k}$, where $k=0,1 \cdots, n$


Your Answer

By clicking “Post Your Answer”, you agree to our terms of service, privacy policy and cookie policy

Not the answer you're looking for? Browse other questions tagged or ask your own question.